A rare pediatric case of bilateral bronchopulmonary vascular malformations and right isomerism. Issue 8 (24th April 2021) - Verma, Mansi; Khurana, Rishabh; Malhi, Amarinder S.; Relan, Jay; Deshpande, Amit Ajit; Kumar, Sanjeev; Kothari, Shyam S.
Abstract: We present an unusual case of an 18‐day‐old term neonate with coexistent bilateral bronchopulmonary vascular malformations and right isomerism. This case highlights the importance of computed tomography angiography in depicting such complex anomalies and classifying them according to components involved providing a systematic approach for evaluation of the disease process.